Maintaining the Uptake of Peritoneal Dialysis During the COVID-19 Pandemic: A Research Letter. (February 2021) - Canney, Mark; Er, Lee; Antonsen, John; Copland, Michael; Singh, Rajinder Suneet; Levin, Adeera
Background: Due to inherent challenges in maintaining physical distancing in hemodialysis units, the Canadian Society of Nephrology has recommended peritoneal dialysis as the preferred modality for patients requiring maintenance dialysis during the coronavirus disease 19 (COVID-19) pandemic. However, pursuing peritoneal dialysis is not without risk due to the requirement for in-person contact during catheter insertion and training, and there is a paucity of data regarding the experience of peritoneal dialysis during the early phases of the pandemic. Objective: To examine the incidence and outcomes of peritoneal dialysis between March 17 and June 01, 2020 compared to the same time period in preceding years. Design: Retrospective observational study. Setting: British Columbia, Canada. After the pandemic was declared on March 17, 2020, patients continued to be trained in peritoneal dialysis. In an effort to limit time spent in hospital, patients were preferentially trained in continuous ambulatory peritoneal dialysis, training times were truncated for some patients, and peritoneal dialysis catheters were inserted by a physician at the bedside whenever feasible. Patients: All patients aged >18 years who started chronic maintenance dialysis during the period March 17 to June 01 in the years 2018 to 2020 inclusive. The time period was extended to include the years 2010 to 2020 inclusive to evaluate longer term trends in dialysis incidence. Measurements: A provincial clinical information system was used to capture the date of commencing dialysis, dialysis modality, and complications including peritonitis. Overall uptake of peritoneal dialysis included new starts and transitions to peritoneal dialysis from in-center hemodialysis during the observation period. Methods: The incidence of dialysis during the specified time period, overall and by modality, was calculated per million population using census figures for the population at risk. Patients were followed for a minimum of 30 days from the start of peritoneal dialysis to capture episodes of peritonitis and COVID-19. Results: A total of 211 patients started maintenance dialysis between March 17 and June 01, 2020. The incidence dialysis rate (41.3 per million population) was lower than that expected based on the 10-year trend from 2010 to 2019 inclusive (expected rate 45.7 per million population, 95% confidence interval 41.7 to 50.1). A total of 93 patients started peritoneal dialysis, including 32 patients who transitioned from in-center hemodialysis, contributing to a higher overall uptake of peritoneal dialysis compared to preceding years. The incidence rate for peritoneal dialysis of 18.2 per million population was higher than that expected (16.3 per million population, 95% confidence interval 14.0 to 19.0). Half of patients (48%) underwent a bedside peritoneal dialysis catheter insertion by a physician. During 30 days of follow-up, 2 (2.2%) patients experienced peritonitis and no patients were diagnosed with COVID-19. Limitations: Results are short term and generalizable only to regions with similarly low community rates of transmission of severe acute respiratory syndrome coronavirus 2. Conclusions: These preliminary findings indicate that peritoneal dialysis can be safely started and perhaps expanded as a means of mitigating the anticipated surge in in-center hemodialysis during the COVID-19 pandemic. Important contributors to the uptake of peritoneal dialysis in British Columbia were bedside catheter insertions and expediting transitions from in-center hemodialysis to peritoneal dialysis.